Komitmen afektif karyawan hotel: Peran berbagi pengetahuan dan kepuasan kerja - Tirto, Andreas Irawan; Wulani, Fenika (Jurnal Manajemen Maranatha, 2024)
This study aims to analyze the effect of knowledge sharing and job satisfaction on the affective commitment of hotel employees working in Surabaya. Data collection was done with a survey questionnaire. This study has 63 respondents. The data analysis was based on multiple linear regressions. Research results show that job satisfaction significantly has a positive effect on affective commitment. This finding means that the higher the job satisfaction, the higher the affective commitment, and vice versa. However, knowledge-sharing behavior has no significant effect on affective commitment. The results of this study show that hotels need to satisfy their employees through various factors such as job design, support from supervisors and coworkers, and recognition and appreciation.